School Segregation Reduces Life Expectancy in the U.S. Black Population by 9 Years (Mary Ann Liebert, 2022)
Despite the 1954 Brown versus Board of Education Supreme Court decision, school segregation of U.S. blacks persists. Given the powerful role of education as a social determinant, health consequences of school segregation are likely to be substantial. This study indicates the causal link between school segregation and high school graduation and the association of graduation and life expectancy. It estimates the reduction in life expectancy associated with school segregation and characterizes the prevalence of school segregation of black students in states. Lack of high school completion is associated with a reduction in life expectancy of 9 years?similar to that of smoking. The prevalence of black school segregation (>50% minority) is greatest in the Northeast (81.1%), next highest in the South (78.1), next in the Midwest (68.4%), and lowest in the West (13.6%). Known remedies to school segregation must be implemented to eliminate this root of health inequity.